International Design and Development of a 1x4 Microstrip Monopole Antenna Array at 5 GHz U-NII-2A Bands (5150 - 5350 MHz) For Wireless Fidelity Devices - Sandya Firstha Nofianti; Yulindon Yulindon; Sahid Ridho; Rezky Cahaya Nabila (International Journal of Wireless And Multimedia Communications, 2026)
High-fidelity antennas are necessary due to the quick advancement of wireless communication technology, particularly for Wireless Fidelity (Wi-Fi) networks. Low antenna gain and a short signal range are two issues that frequently arise in Wi-Fi networks and can degrade the quality of data transmission. Consequently, an antenna design that can increase the overall system fidelity is required, particularly in the 5 GHz frequency band that is frequently utilized by Wi-Fi modem devices. This final project involves designing and developing a 1x4 microstrip monopole antenna array for Wireless Fidelity (Wi-Fi) devices that operate at the 5 GHz U-NII-1 and U-NII-2A bands (5150–5350 MHz). In order to facilitate Wi-Fi data transmission, this design aims to create an antenna with a higher gain, denser bandwidth, and appropriate radiation coverage. CST Studio Suite 2019 software was used to carry out the design on an FR4 substrate that was 1.6 mm thick and had a dielectric constant of 4.3. A Vector Network Analyzer (VNA) was then used to simulate, optimize, fabricate, and measure the design. With a simulated return loss of -51 dB, a VSWR of 1, and a bandwidth of 1 GHz with a bidirectional radiation pattern, the simulation and measurement results of the antenna demonstrate good performance. According to the measurement results, the bandwidth is 1.1 GHz, the VSWR is 1.2, and the return loss is -20 dB. The simulation and fabrication results demonstrate good suitability and conform to the requirements for creating Wi-Fi microstrip antennas.